Moving Towards Equity in the Arts Is America’s Silicon Valley a Cultural Backwater or Harbinger? - Borrup, Tom; Wagner, Heidi; Taing, Elizabeth; Rawson, Amanda (Journal of Urban Culture Research, 2021)
During a time when American cultural institutions and their funders have committed to advancing cultural equity and reverse patterns of white supremacy, this study illustrates a possible scenario of what that might look like. The nonprofit arts and cultural landscape observed in Silicon Valley raises questions of how American cities and regions might look in their movement towards equity. Data on these nonprofit organizations in this California region were examined in 2019 and compared with data from a decade earlier. These included numbers and start-up years of nonprofit arts and cultural organizations, their types, expenditures, and mission-based focus. In addition to a decade of change within this landscape, it was contrasted with nine other U.S. city-regions. We found Silicon Valley decidedly different from its peers. In spite of its large central city of San José, and a metropolitan population of over three million, there are comparatively few large institutions representative of Western-European cultures in Silicon Valley. In fact, the number of such organizations and their expenditures declined significantly while in other regions such organizations grew, often substantially. At this same time, smaller, culturally specific organizations in Silicon Valley grew significantly revealing an entrepreneurial region with a high percentage of new organizations more closely aligned with the diversity of the its population.